How often are major blood-borne pathogens found in eye patients? A serosurvey at an eye hospital in Southern China. - Fang Duan (Public Library of Science (PLoS), 2013)
Background The hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV) and treponema pallidum (TP) are blood-borne pathogens. They can lead to nosocomial and occupational infections in health care settings. We aimed to identify the prevalence of and risk factors associated with HBV, HCV, HIV and TP infections among patients with eye diseases at a tertiary eye hospital in Southern China. Methods From July 2011 to June 2012, a total of 26,386 blood units were collected from eye patients, including inpatients and the day surgery patients at Zhongshan Ophthalmic Center, one of the biggest eye hospitals in China. Based on the primary diagnoses from this period, the subjects were classified into different ocular disease groups. All blood samples were tested for HBsAg, anti-HCV, anti-HIV and anti-TP. Result The overall prevalence of HBV, HCV, TP and HIV was 9.79%, 0.99%, 2.43% and 0.11%, respectively. The prevalence of HBsAg was much lower among patients younger than 20 years compared to other age groups. In addition, the risk of HBsAg was associated with the male gender, ocular trauma and glaucoma. The prevalence of TP increased with age and the prevalence among patients older than 30 was higher than that in patients younger than 20 years. Conclusions The prevalence of HBV, HCV, HIV and TP in patients with eye diseases was identified. This information can be utilised to strengthen the health education and implementation of universal safety precautions to prevent the spread of blood-borne pathogens in health care settings.